Review and simulation of leakage current in transformerless microinverters for PV applications. (July 2017) - Khan, Ahmad; Ben-Brahim, Lazhar; Gastli, Adel; Benammar, Mohieddine
Abstract: Designing microinverters without transformers enhances system efficiency and power density and reduces cost. However, the transformer removal results in loss of galvanic isolation that leads to leakage current circulation. Recently, there has been wide concern about this leakage current circulation and solutions have been proposed for its reduction. The objective of this paper is to investigate the circulating leakage current of different microinverters, its generation mechanism, and its mitigation techniques. In order to have an objective comparison between the different topologies and their leakage current mitigation techniques, simulations were carried out using identical system parameters and operating conditions for all topologies under investigation. The results show that among all the topologies that use additional switches to mitigate the leakage current, the HERIC NPC types and DC-based NPC microinverters produce the lowest leakage current. Furthermore, recent development in this area shows that the leakage current could be also mitigated with just passive filters.